A decoupling structure without sacrificing antenna‐element performance for 5G smartphone designs. Issue 9 (24th May 2022) - Luo, Yi; Zhu, Lei; Liu, Ying; Gong, Shuxi
Abstract: Operating frequencies and isolation are two critical parameters for 5G smartphone antennas. However, most of the existing decoupling methods will cause the unexpected variations on the performance of antenna element, such that the designers have to spend a lot of time to adjust the configuration of antenna element again and again for the purpose of maintaining the desired performance. To address this issue, a decoupling structure, which introduces another path for canceling the coupling, is proposed in this work. Such method is helpful in achieving the high isolation between two coupled antenna elements without sacrificing the radiating‐mode performance and geometrical configuration of each individual antenna element. Under this method, an open‐slot antenna pair operating at the sub‐6 GHz band of 3.3–3.6 GHz is designed and an isolation higher than 11 dB is obtained. This decoupling method is capable of not only maintaining the original self‐performance of each antenna element but also attaining good isolation between two elements. Owing to this attractive feature, the proposed method is promising for supporting the design of antenna element and decoupling structure in two separate steps, which might save a lot of time in the future design of a large array or massive MIMO.